A Wireless Sensor Network Testbed for the Evaluation of Energy-Aware Routing Schemes - Magdalena J. Grobler; Henri-Jean Marais; Joubert G. J. Krige (International Journal of Distributed Sensor Networks)
Wireless sensor networks (WSNs) are receiving a lot of research attention due to continual improvement in the technologies used by these networks. The energy efficiency of sensor nodes and the network as a whole is of specific importance. One possible area where energy savings can be made lies within the routing protocols employed; however, these protocols are typically only simulated. In this work we develop a WSN testbed and conduct investigations on the fidelity of simulated energy-aware WNS routing protocols. It was found that the real-world performance of these energy-aware protocols was significantly lower than that predicted by simulation models. This can be mainly attributed to chip-level effects not taken into account by simulation models, leading to simulated results that cannot be achieved in real-world deployments. This work illuminates the shortfalls of existing simulation models and suggests ways in which these models can be improved. Additionally the testbed allows other energy-aware routing protocols to be investigated easily.